2020
DOI: 10.3389/fpsyg.2020.01202
|View full text |Cite
|
Sign up to set email alerts
|

Proof of Concept of a Gamified DEvelopmental Assessment on an E-Platform (DEEP) Tool to Measure Cognitive Development in Rural Indian Preschool Children

Abstract: Over 250 million children in developing countries are at risk of not achieving their developmental potential, and unlikely to receive timely interventions because existing developmental assessments that help identify children who are faltering are prohibitive for use in low resource contexts. To bridge this "detection gap," we developed a tablet-based, gamified cognitive assessment tool named DEvelopmental assessment on an E-Platform (DEEP), which is feasible for delivery by non-specialists in rural Indian hou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…We have demonstrated that our innovative tools allow us to take gamified assessments of child developmental capabilities into the hands of frontline workers and assess young children in the comfort of their own home while they interact with evidence-based engaging assessments (Bhavnani et al, 2019). We have also shown that these assessments fare well against the gold standards of child development assessments (Mukherjee et al, 2020). Our efforts have led to the creative integration of diverse assessment technologies, for example, designing the lead character of the DEEP games to be a child who wears a special cap has facilitated the child being assessed to agreeing to wear a portable EEG cap, thus allowing us to collect both the digital game data and EEG data simultaneously.…”
Section: Ll Open Accessmentioning
confidence: 91%
“…We have demonstrated that our innovative tools allow us to take gamified assessments of child developmental capabilities into the hands of frontline workers and assess young children in the comfort of their own home while they interact with evidence-based engaging assessments (Bhavnani et al, 2019). We have also shown that these assessments fare well against the gold standards of child development assessments (Mukherjee et al, 2020). Our efforts have led to the creative integration of diverse assessment technologies, for example, designing the lead character of the DEEP games to be a child who wears a special cap has facilitated the child being assessed to agreeing to wear a portable EEG cap, thus allowing us to collect both the digital game data and EEG data simultaneously.…”
Section: Ll Open Accessmentioning
confidence: 91%
“…Cognition at 3-years of age: The Bayley's Scale of Infant and Toddler Development, 3rd Edition (BSID-III), a developmental assessment for preschool children aged 0–42 months [24] , was administered on the 200 participants described above. A translated version of the BSID-III adapted for administration by non-specialists was used following a protocol described previously [ 15 , 22 ]. Raw scores were computed as per the manual, and used to generate age-adjusted composite scores.…”
Section: Methodsmentioning
confidence: 99%
“…DEEP has been piloted on a cohort of children in a rural north Indian region and demonstrated to be highly engaging for children across genders, acceptable to their parents and feasible for delivery by trained non-specialist personnel in the comfort of the child's home [14] . A proof-of-concept study has also demonstrated that it is possible to predict children's score on the cognitive domain of the Bayley's Scale for Infant and Toddler Development (BSID – IIIrd edition), using metrics captured by DEEP [15] . This study used a supervised machine learning approach benchmarked to the BSID-III cognitive score to develop an algorithm comprising a combination of features extracted from a child's performance on different DEEP games to derive the DEEP cognitive score.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, a recent study followed an unselected sample of children from age 8 to late adolescence, collecting a large number of measures including neurocognitive tests and symptoms; children who developed psychotic symptoms later in adolescence were on average 1–2 years behind typically-developing children in cognitive growth, suggesting that early cognitive impairment could be a marker for psychosis risk and that growth charting may be an opportunity for early detection and prevention ( 24 ). Another group has independently begun to implement this concept with a developmental battery of “gamified” tasks (running on a mobile e-platform) that assesses six cognitive domains in young children in India as a first step to developing normative growth curves ( 25 ).…”
Section: Rdoc and The Psychotic Spectrummentioning
confidence: 99%